2021
DOI: 10.4103/ijo.ijo_1585_21
|View full text |Cite
|
Sign up to set email alerts
|

Validation of choroidal hyperreflective foci in diabetic macular edema through a retrospective pilot study

Abstract: Purpose: Choroidal hyperreflective foci (HCF) are novel spectral-domain optical coherence tomography (SDOCT) biomarkers in diabetic macular edema (DME). The present study intended to validate HCF and assess their role in the treatment outcome. Methods: It was a retrospective, longitudinal, records-based pilot study recruiting consecutive patients of nonproliferative diabetic retinopathy with treatment naïve DME. Patients were treated with three intravitreal anti-vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Intraretinal HRF have been characterized in several diseases, such as diabetic macular oedema (Saurabh et al, 2021), angioid streaks (Romano et al, 2019) and age‐related macular degeneration (Nassisi et al, 2018). Conversely, choroidal HRF have been seldom explored and have been interpreted as lipofuscin deposits (Piri et al, 2015; Saurabh et al, 2021), macrophages (Kim & Oh, 2022; Romano et al, 2020), degenerated RPE cells (Romano et al, 2020) or melanocytes (Kim & Oh, 2022). Hyperreflectivity on OCT is an optical property of different molecules, and we cannot univocally conclude on HRF composition.…”
Section: Discussionmentioning
confidence: 99%
“…Intraretinal HRF have been characterized in several diseases, such as diabetic macular oedema (Saurabh et al, 2021), angioid streaks (Romano et al, 2019) and age‐related macular degeneration (Nassisi et al, 2018). Conversely, choroidal HRF have been seldom explored and have been interpreted as lipofuscin deposits (Piri et al, 2015; Saurabh et al, 2021), macrophages (Kim & Oh, 2022; Romano et al, 2020), degenerated RPE cells (Romano et al, 2020) or melanocytes (Kim & Oh, 2022). Hyperreflectivity on OCT is an optical property of different molecules, and we cannot univocally conclude on HRF composition.…”
Section: Discussionmentioning
confidence: 99%
“…In the study[ 8 ] published in the current issue, the authors have gone one step further in trying to validate the role of HCF in patients of NPDR with treatment-naïve DME following treatment with anti-VEGFs. They have reported that presence of HCF was associated with worse initial VA compared to the eyes that had HRF alone, and the difference was statistically significant.…”
mentioning
confidence: 99%